Primary hyperparathyroidism in Saudi Arabia revisited: a multi-centre observational study - Yousef Al-Saleh; Abdullah AlSohaim; Reem AlAmoudi; Ali AlQarni; Raed Alenezi; Layla Mahdi; Hend Alzanbaqi; Samah M. Nawar; Hibah AlHarbi; Abdulrhman ALMulla; Maryam Al Qahtani; Salih Bin Salih; et al. (BMC Endocrine Disorders, 2022)
Abstract Purpose Primary hyperparathyroidism (PHPT) is a common cause of hypercalcemia and remains understudied within the Arabian population. The present study, the largest of its kind within the Gulf Cooperation Council (GCC) countries, aims to determine the demographics and clinical presentation of PHPT in Saudi Arabia. Methods In this multi-center retrospective study involving three tertiary hospitals in different geographic locations of Saudi Arabia namely, Riyadh, Al Ahsa and Jeddah, a total of 205 out of 243 confirmed PHPT cases aged 16 to 93 years old were included (N = 96 from Riyadh; N = 59 from Al Ahsa and N = 50 from Jeddah). Demographics, clinical manifestations and surgical outcomes were recorded as well as laboratory and radiologic investigations including serum parathyroid hormone (PTH), 25(OH)D, adjusted calcium, estimated glomerular filtration rate (eGFR) and nuclear scan outcome. Results PHPT cases appeared to increase over time when compared to other local studies published so far, with 12.8 cases per 100,000 hospital population. Females outnumber males (3:1) with 86% seen as out-patients. The average age was 59.8 ± 15.5 years. Abnormal PTH scan was seen in 171 patients (83.4%). Kidney stones was the most common renal manifestation (32 cases, 15.6%) and osteoporosis was the most common skeletal manifestation (67 cases, 32.7%). Al Ahsa had the highest prevalence of multiple comorbidities at 54% and the highest prevalence of obesity as a single comorbidity (17%) compared to other regions (p < 0.05). Jeddah recorded the highest prevalence of osteoporosis with bone and joint pains (30%) (p < 0.05). Conclusion Comparison of present data with previous local studies suggest an increasing trend in PHPT cases in Saudi Arabia. Regional variations in the clinical presentation of PHPT were observed and warrant further investigation.